The effects of grape seed proanthocyanidins in cafeteria diet-induced obese Fischer 344 rats are influenced by faecal microbiota in a photoperiod dependent manner. Issue 16 (2nd August 2022) - Arreaza-Gil, Verónica; Escobar-Martínez, Iván; Muguerza, Begoña; Aragonès, Gerard; Suárez, Manuel; Torres-Fuentes, Cristina; Arola-Arnal, Anna
Abstract : GSPE anti-obesity effects are modulated by the gut microbiota in a photoperiod-dependent manner. Abstract : Polyphenols are of high interest due to their beneficial health effects, including anti-obesity properties. The gut microbiota may play an important role in polyphenol-mediated effects as these bacteria are significantly involved in the metabolism of polyphenols. Moreover, seasonal rhythms have been demonstrated to influence both the gut microbiota composition and polyphenol bioavailability. Thus, the goal of this study was to evaluate the impact of photoperiods and microbiota on polyphenol functionality in an obesogenic context. Towards this aim, cafeteria diet-fed Fischer 344 rats were housed under three different photoperiod conditions (L6: 6 h of light, L12: 12 h of light and L18: 18 h of light) for 9 weeks. During the last 4 weeks of the experiment, rats were daily administered with an oral dose of a grape seed proanthocyanidin extract (GSPE) (25 mg per kg body weight). Additionally, rats treated with GSPE and an antibiotic cocktail (ABX) in their drinking water were included for a better understanding of the gut microbiota role in GSPE functionality. Vehicle and non-ABX treated rats were included as controls. GSPE decreased body weight gain and fat depots only under L18 conditions. Interestingly, the gut microbiota composition was strongly altered in this photoperiod. GSPE + ABX-treated rats gained significantly less body weight compared to the rats of the rest of the treatments under L18 conditions. These results suggest that GSPE functionality is modulated by the gut microbiota in a photoperiod dependent manner. These novel findings corroborate seasonal rhythms as key factors that must be taken into account when investigating the effects of polyphenols in the treatment or prevention of chronic diseases.